Integration of Digital Marketing and Entrepreneurship in Building a Competitive Local Brand - Riani Ishak; Heni Widyaningsih; Sulaiman Mansyur; Syurwana Farwita Samuddin; Alexander Setiawan (Westscience Press, 2025)
This study explores the integration of Digital Marketing and Entrepreneurship in building competitive local brands within Indonesia's creative economy. Using a quantitative approach, data was collected from 110 respondents using a Likert scale survey, and analyzed through SPSS version 25. The research aimed to investigate how digital marketing strategies and entrepreneurial behavior contribute to brand competitiveness in the context of small and medium enterprises (SMEs). The results showed that both Digital Marketing and Entrepreneurship have a significant positive effect on Brand Competitiveness, with Digital Marketing having a slightly stronger impact. The model accounted for 65.9% of the variance in brand competitiveness, emphasizing the importance of leveraging digital tools alongside entrepreneurial strategies. The study highlights that integrating digital marketing with entrepreneurial innovation is key to strengthening local brands and enhancing their competitive advantage in Indonesia's rapidly growing creative economy.